Vermicompost and Mycorrhizae Use on Cedrela odorata L. Growth in Nursery Conditions (Agro Productividad, 2021)
Objective: To evaluate the effect of mycorrhizal inoculation and the use ofvermicompost on the growth of red cedar (Cedrela odorata L.) seedlings under nurseryconditions.Materials and Methods: The treatments were with and without a Glomus intraradicesinoculum, combined with different amounts of vermicompost in the growth substrate (0,10, 20 and 30 %), in a completely randomized block design. The variables evaluatedwere plant height (PH), stem diameter (SD), number of leaves (NL), dry weight (DW),mycorrhizal colonization (MC) and number of spores (NS).Results: The addition of vermicompost to the growth substrate improved the growth ofC. odorata seedlings, the best treatment being 30% of vermicompost withoutmycorrhizae. The percentage of mycorrhizal colonization and number of spores per 100g of soil decreased when increasing the amount of vermicompost in the substrate.Study Limitations/Implications: None.Findings/Conclusions: Vermicompost was the leading promoter of C. odorata plantgrowth under nursery conditions.